KNOWING YOUR ROOTS: ENHANCING ORAL PROFICIENCY OF ELEMENTARY STUDENTS IN KURDISTAN USING ORAL PRESENTATION AS AN ALTERNATIVE ASSESSMENT IN THE ‘FAMILY TREE’ TASK (Practitioner Research, 2022)
This paper aims at presenting the specifics of designing oral presentations as an alternative assessment for elementary students in Kurdistan. Being non-native speakers of English, oral proficiency is an increasingly significant aspect of language teaching among young Kurdish learners. Thus, the purpose of oral presentation in the ‘Family Tree’ task is to build students’ confidence in speaking a foreign language (English language) among young non-native speakers in a creative and comfortable learning environment. It also increases communication among students and the teacher by encouraging students to easily share what they have learned in class. However, previous research has criticized oral examinations for lack of reliability and validity. Consequently, the current research seeks to design a reliable and valid alternative assessment by incorporating the Family Tree task into an oral presentation. To measure students’ oral communication skills, a “Task-Specific” scoring rubric was designed to evaluate students’ performances with four essential dimensions; (1) Vocabulary, (2) Pronunciation, (3) Task, and (4) Fluency. Data were obtained from two elementary classes of a public school located in Dohuk in Kurdistan among 13 boys and 14 girls. The student consists of fourth and fifth-grade students within the range of 9 to 10 years old. The result shows that assessing students using the oral presentation as an alternative assessment escalates students’ confidence and motivation to speak publicly as the examination setting becomes less threatening and that oral presentation using a rubric allows detailed identification of students’ areas of improvement for elementary school students.